Automatización de sistema modular de elevación inalámbrico para vehículos pesados (2020)
This document presents the automation of a distributed lifting jack system for heavy vehicles, more exactly for train engines and wagons. The proposed system is composed by a number of controlled columns synchronized to produce the desired trajectory. The synchronization is necessary to guarantee the leveled motion of the load, to avoid drawbacks due to unbalanced loading. Two synchronization strategies were tested: first, adjust the trajectory by subtracting the difference between column heights from that of a particular column. Second, reduce the speed of the columns more advanced with respect to a special column to level all at the height of the latter. Each column is simulated including the lifting jack (a power screw with a velocity reduction system) driven by a servo motor with its amplifier controlled by a PD. The simulation results are compared in terms of motion discrepancies among the columns, considering the limitations of energy consumption.